2015
DOI: 10.1007/s10772-015-9290-8
|View full text |Cite
|
Sign up to set email alerts
|

A frame-based approach for capturing semantics from Arabic text for text-to-sign language MT

Abstract: This paper describes the design and implementation of a computational model for Arabic natural language semantics, a semantic parser for capturing the deep semantic representation of Arabic text. The parser represents a major part of an Interlingua-based machine translation system for translating Arabic text into Sign Language. The parser follows a frame-based analysis to capture the overall meaning of Arabic text into a formal representation suitable for NLP applications that need for deep semantics represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Ismail et al (2022) presented a new alignment word-space approach for snipped text similarity. Lakhfif and Laskri (2016) described the design and implementation of a computational model for an Arabic semantic parser that could create a deeper semantic representation of Arabic text. They showed that the integration of WordNet and FrameNet can improve disambiguation accuracy.…”
Section: Examples Of How To Pick a Good American President From 2016 ...mentioning
confidence: 99%
“…Ismail et al (2022) presented a new alignment word-space approach for snipped text similarity. Lakhfif and Laskri (2016) described the design and implementation of a computational model for an Arabic semantic parser that could create a deeper semantic representation of Arabic text. They showed that the integration of WordNet and FrameNet can improve disambiguation accuracy.…”
Section: Examples Of How To Pick a Good American President From 2016 ...mentioning
confidence: 99%
“…FrameNet (FN) was developed in an effort to build a lexicon of English that is comprehendible by both human and machine, using the theory of frame semantics and backed by means of an annotated corpus of lexical items (Baker, 2014;Fillmore et al, 2003;Lakhfif & Laskri, 2015). The knowledge base structure of FN is defined as a relation between frames at various levels of generality.…”
Section: Framenetmentioning
confidence: 99%
“…The annotation process involves FN lexicographers to declare each word in a sentence as a target, then select a frame related to the target, get a set of annotation layers and appropriate frame element tags and the annotate the relevant constituents (Ruppenhofer et al, 2006). FN version 1.3, is a freely available lexical database which contains a wealth of semantic knowledge of about 1161 Semantic Frames, covering more than 12,600 lexical units, documented with nearly 200,000 manual annotations (Lakhfif & Laskri, 2015). FN is developed based on the eXtensible Markup Language (XML) (Martínez-Santiago et al, 2015).…”
Section: Framenetmentioning
confidence: 99%
“…For Arabic video text recognition, this paper uses the same sequence to sequence model. A great deal of work has been carried out in [16,17] to recognize video text. The availability of Arabic script datasets is minor compared to English script datasets, but for video text recognition, two datasets are available: the ACTIV dataset [18] and the ALIF dataset [19].…”
Section: Introductionmentioning
confidence: 99%